The Role of Quipper Application for English Language Teaching - Mizal, Basidin; Tathahira, Tathahira (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2022)
Quipper is one of widely recognised Online Learning Platforms for learners on many levels. Quipper is equipped with several features that can support the process of learning, especially for language learning. This study aims to deeply discuss the features offered by Quipper that can benefit the learners through suitable instructional design used in learning English; and to provide the implication of its use for Indonesian education context. This study is library research where the data were derived from relevant articles and previous studies. The research findings revealed that some features of Quipper could benefit students to acquire new vocabulary, punctuality and grammatical awareness through Chat Room or In-built Messaging. Moreover, as web-based learning platform, Quipper could expose the multimodal exposure (written, oral and visual) for foreign language input. More importantly, Quipper was interestingly viewed by many learners as a new way of learning that somehow could enhance their positive language learning intensity. Nevertheless, even though Quipper is positively welcomed, it might imply several challenges and limitations. In Indonesian education context, Quipper could not be fully used as the main platform for learning because there would be a great reliance on teachers to misuse the features that leading to the boring class activity and lack of teaching professionalism.